Ceres - Smith, L. Neil (Phoenix Pick, 2009)
"In the 22nd century people have spread into the Solar System. Born and raised in a twentieth of Earth's gravity on the asteroid Pallas, young skater Llyra Ngu is grimly determined to compete and win on mankind's homeworld- an ambition that many say will cripple or kill her. Her older brother Wilson is equally set on quitting his job as a surveyor's apprentice to become an asteroid hunter, a calling fraught with the promise of fabulous riches and the danger of sudden death. He will find a full share of romance and disappointment, love and loss, and pursue the asteroid hunter's holy grail, the legendary Diamond Rogue."-- back cover